Application and Development of Shape Memory Micro/Nano Patterns. Issue 13 (16th December 2021) - Li, Wenbing; Liu, Junhao; Chen, Lei; Wei, Wanting; Qian, Kun; Liu, Yanju; Leng, Jinsong
Abstract: Shape memory polymers (SMPs) are a class of smart materials that change shape when stimulated by environmental stimuli. Different from the shape memory effect at the macro level, the introduction of micro‐patterning technology into SMPs strengthens the exploration of the shape memory effect at the micro/nano level. The emergence of shape memory micro/nano patterns provides a new direction for the future development of smart polymers, and their applications in the fields of biomedicine/textile/micro‐optics/adhesives show huge potential. In this review, the authors introduce the types of shape memory micro/nano patterns, summarize the preparation methods, then explore the imminent and potential applications in various fields. In the end, their shortcomings and future development direction are also proposed. Abstract : The emergence of shape memory micro/nano patterns provides a new direction for the future development of smart polymers, and shows huge application potential in the fields of biomedicine/textile/microoptics/adhesives. This review introduces the types of shape memory micro/nano patterns, summarizes the preparation methods, explores the imminent and potential applications, and proposes their shortcomings and future development direction.